(untitled) (Research, Society and Development, 2022)
To analyze the cases of sexual violence reported in the reference service of the Hospital e maternity Dona Regina in the city of Palmas Tocantins and, with that, to characterize the profile of the victims and the outcome of the injuries. It is then possible to categorize the types of sexual violence, the reported sexual practices, their relationship with other types of violence, the place of occurrence, the number of aggressors involved, the most affected gender and the bond between the aggressor and the victim to promote policies public safety measures to prevent new occurrences. Methods: This is pure scientific research, with exploratory and descriptive analysis regarding its objectives, and quantitative analysis through documental analysis of medical records of the Specialized Attention Service for People in Situations of Sexual Violence (SAVIS) and data from the Notifiable Diseases Information System (SINAN) of the Dona Regina Hospital and Maternity Hospital from January 2018 to December 2020. Results: 733 occurrences were computed, with the profile of the victims: being young female adolescents, students, still with low schooling, mixed race/color. The cases occurred predominantly in residences, with the majority of male aggressors. Rape was the prevalent form of sexual violence, followed by beatings, threats, hanging and the use of weapons. Conclusion: The characterization of victims of sexual violence is essential to guide an intervention proposal.